2019
DOI: 10.3390/su11216141
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of TBT and SPS Measures on Japanese and Korean Exports to China

Abstract: (1) Background: As countries with troubled histories, China, Japan, and Korea have, in recent times, attempted to overcome political and economic differences in a bid to forge strong trade relationships. However, Non-Tariff Measures (NTMs) have emerged in recent times, which has the potential to complicate matters. (2) Method: Our study analyzes the impact that two forms of NTM, technical barriers to trade (TBT) and sanitary and phytosanitary measures (SPS), have on Japanese and Korean exports to China. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
(46 reference statements)
3
15
0
4
Order By: Relevance
“…However, these results contradict those of Santeramo et al [37], who found that INSP and TBT encouraged wine imports for China. In addition to Santeramo et al [37], several other researchers have proved that NTMs do not necessarily harm trade; they can also have positive impacts on trade [20,23,38]. Ghodsi and Stehrer [23] found that SPS measures imposed by the EU significantly increased dairy trade values and quantities.…”
Section: Literature Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…However, these results contradict those of Santeramo et al [37], who found that INSP and TBT encouraged wine imports for China. In addition to Santeramo et al [37], several other researchers have proved that NTMs do not necessarily harm trade; they can also have positive impacts on trade [20,23,38]. Ghodsi and Stehrer [23] found that SPS measures imposed by the EU significantly increased dairy trade values and quantities.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The increasing significance of NTMs as trade policy measures has attracted policymaker and researcher attention to NTM implementation and the impact on international trade flows [4,[12][13][14][15][16][17][18][19][20]. Most authors have focused on the impact of NTM liberalization through free trade agreements (FTAs), as NTMs are commonly assumed to distort trade [12,15,[31][32][33].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the added value formed can be distributed to domestic economic actors. In the world trade system, the SPS (sanitary and phytosanitary) instruments and customs procedures applied in world trade have become obstacles (obstacles) to the flow of trade between countries [13]. This condition caused a decline in demand for Indonesian nutmeg in the European market in 2011-2012 [14].…”
Section: Indonesia's Nutmeg Export Performancementioning
confidence: 99%